REMOTE ADMINISTRATION TOOL (RAT) FOR ANDROID - MOHAMAD SAIR, MUHAMMAD SHARIFUDDIN BIN (Journal of Computing Technologies and Creative Content, 2019)
Remote Administration Tool (RAT) allowing an admin to remotely control the android device. A Remote Administration Tool is remote control software that when installed on an android device it allows a computer to take control of it. A Remote Administration Tool (RAT) allows an admin to remotely control an android device and typically consists of a server invisibly running and listening to specific socket TCP/UDP ports on an admin machine as well as a client acting as the interface between the server and the client.